Investigation of the causative agents of the 1982 Gazankulu poliomyelitis outbreak, using four biochemical techniques - Gibson, Katherine Margaret (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1989)
Comparison of poliovirus strains was carried out to determine the origin of the virus in two isolates obtained during the 1982 outbreak of poliomyelitis in Gazankulu. Comparisons of the outbreak isolates with vaccine and wild-type strains of the same poliovirus type were carried out using four biochemical techniques. SDS-polyacrylamide gel electrophoresis (SDS-PAGE), two-dimensional thin-layer chromatography (TLC) and reversed-phase high-performance liquid-chromatography (RP-HPLC) were used for comparing viral capsid proteins. Comparison of poliovirus strains at a genetic level was carried out using two-dimensional oligonucleotide mapping of viral RNA. Results showed the type 1 poliovirus isolate, 5061, to be a novel wild-type poliovirus. The type 2 isolate, 5068, was closely related to the poliovirus type 2 Sabin vaccine strain, P712. It was concluded that the intrinsic variability of poliovirus strains was responsible for the appearance of isolate 5068
Keywords: Poliomyelitis -- Analysis; Poliomyelitis -- History -- South Africa; Poliomyelitis vaccine -- Analysis